Microprocessor-Based Memory Device for Ambulatory Heart Rate and Physical Activity Recording - Makikawa, M.; Imai, K.; Shindoi, T.; Tanooka, K.; Iizumi, H.; Mitani, H. (Methods of Information in Medicine, 1994)
Using microprocessor techniques, a portable digital memory device has been designed for the ambulatory monitoring of heart rate and physical activity. The device consists of a microprocessor, an ECG amplifier to record the heart rate and an accelerometerto detect the physical activity. This accelerometer is piezoresistive and is suitable for ambulatory physical activity recording, because this sensor requires low electrical power, has high durability and wide frequency response (DC~1.2 kHz). Changes in hearti rates and physical activity in daily life have been successfully recorded.
Keywords: Ambulatory Monitoring; Microprocessor; Heart Rate; Physical Activity